Diabetes Mellitus Tipe 2: Prevalensi, Etiologi, dan Penatalaksanaannya - Naki, Maulana Isman; Sumariangen, Ayu Brenda; Tambengi, Rizkhy Agung (YCMM, 2025)
Non-Communicable Diseases (NCDs), such as Diabetes Mellitus (DM), are chronic conditions not transmitted between individuals, often caused by unhealthy lifestyles, poor environmental factors, or genetics. With 536.6 million cases globally, DM is a significant health concern, particularly in Indonesia, due to its serious complications if left unmanaged. This literature review examines scientific articles, textbooks, and official publications to explore the prevention and treatment of DM, particularly Type 2 Diabetes Mellitus (T2DM). T2DM, also known as Non-Insulin Dependent Diabetes Mellitus (NIDDM), results from impaired insulin secretion by pancreatic β-cells and reduced tissue sensitivity to insulin. The condition poses a significant risk for complications such as cardiovascular disease, nephropathy, and retinopathy. Despite its prevalence, diagnosis often goes unnoticed due to mild or absent symptoms and relies on blood glucose and HbA1c levels. Effective management includes lifestyle modifications like increased physical activity and healthy dietary patterns, along with tailored pharmacological treatments. New drug classes, including SGLT2 inhibitors and GLP-1 receptor agonists, offer additional benefits, such as weight loss and cardiovascular protection, highlighting advancements in treatment options.